When too many are not enough: Human resource slack and performance at the Dutch East India Company (1700–1795) - Sgourev, Stoyan V; van Lent, Wim (Human relations (New York), 2017)
Slack is an elusive concept in organizational research, with studies documenting a variety of relationships between slack and firm performance. We advocate treating slack not as a resource, but as a practice – a sequence of events and responses over time. A longitudinal analysis of the Dutch East India Company (1700–1795) highlights the use of slack as a response to a resource constraint (the shortage of skilled labor). After documenting the negative performance effects of skill shortage, we identify a trade-off in the use of human resource slack (number of sailors above what is operationally required), in which slack enhanced operational reliability, but reduced efficiency. Derived from a historical context, this trade-off has contemporary relevance and is helpful in reconciling contradictory evidence on slack.